Information technology governance practices in Malaysian public sector - Maidin, Siti Sarah; Arshad, Noor Habibah (IEEE, 2010)
Organizations need to establish effective IT governance practices in order to stay competitive. The aim of this research is to determine the extent of IT governance practices in Malaysian public sector and to determine factors contributes towards IT governance practices. Questionnaire was constructed and distributed to IT management level personnel in public agencies in Klang Valley and Putrajaya. From the findings, it can be noted that 65.7 percent (65.7%) of the respondents has practiced IT governance in their organizations. There were several factors being identified as contributors towards IT governance practices such as senior management involvement in IT, corporate performance measurement systems, corporate communications systems, risk management, strategic alignment, value delivery, ethics/culture of compliance and resource management. Thus, the findings and discussion in this paper could assist Malaysian public sector to incorporate effective IT governance practices in their daily operation.